2000
DOI: 10.1207/s15327957pspr0404_5
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Nature of Cultural Identity Throughout Cultural Transitions: Why Home Is Not So Sweet

Abstract: This article describes the social psychological process that underlies the cultural transition of sojourners. Herein the empirical and theoretical literature on cultural transitions (and in particular cultural repatriation and the relevant literature on self-concept and identity) is analyzed, critiqued, and synthesized in an attempt to understand the near ubiquitous distress experienced during repatriation. The relation among self-concept, cultural identity, and cultural transitions is explored, and in light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
253
1
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(275 citation statements)
references
References 103 publications
9
253
1
12
Order By: Relevance
“…Now we get to the sojourner issue: What happens when you leave your home country to live and study or work in another country? I have suggested a model to think about sojourners which examines cultural identity and its changes throughout the cultural transition cycle (Sussman, 2000). The figure at the end of this chapter shows the important factors and the time line.…”
Section: Introductionmentioning
confidence: 99%
“…Now we get to the sojourner issue: What happens when you leave your home country to live and study or work in another country? I have suggested a model to think about sojourners which examines cultural identity and its changes throughout the cultural transition cycle (Sussman, 2000). The figure at the end of this chapter shows the important factors and the time line.…”
Section: Introductionmentioning
confidence: 99%
“…Sussman (2000) outlines a number of variables which can effect repatriation into the home environment. In her study, Sussman found that factors like the in ability to adapt and low self-esteem will negatively affect the identity upon return to the home country.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the stage where she will confirm which linguistic community she will join and which specific new linguistic identity she will integrate. While at the anticipatory categorization stage, she had focused on the similarities between her old and new linguistic identities when considering which linguistic group she will join in the Québec context, the actual contact with her new group will now allow her to clearly appreciate the distinctiveness of the Québécois Francophone and Russian identities (see Sussman, 2000).…”
Section: Categorizationmentioning
confidence: 99%
“…Indeed, crosscultural contact in the early stages of intercultural contact enables newcomers to isolate the ethnic characteristics typical to their in-group as they discover and acknowledge who they are in the face of the other culture (Stodolska & Yi, 2003). Similarly, Sussman (2000) reports that one of the first process involved in cultural transitions is identity salience where "outgroup membership appears to strengthen, at least initially, our identification with our home culture" (p. 363). Given the all-or-none identification processes operating in this categorization stage, the Russian immigrant is likely to feel that she is primarily Russian rather than being Québécoise Francophone.…”
Section: Categorizationmentioning
confidence: 99%